Knuckles [videorecording (Blu-Ray + DVD)] - Pally, Adam, 1982- (Paramount, 2024)
The new live-action series will follow Knuckles on a hilarious and action-packed journey of self-discovery as he agrees to train Wade as his protégé and teach him the ways of the Echidna warrior.